Continuity and change: understanding livelihood shifts and adaptation in coastal Belize 1830–2012. Issue 2 (1st February 2016) - Karlsson, Marianne; Bryceson, Ian
Abstract : This paper situates livelihood adaptations in two coastal villages within the broader context of Belize's colonial and post-colonial history and environmental processes of change. Through observations, qualitative interviews, and archival reviews, we explore the dynamics of livelihood change and analyse the diverse factors that have been influencing options and adaptation over time. The results reveal that both villages have undergone profound changes in livelihoods and productive activities on several occasions. While the villages' histories, geographies, and cultures are different, similarities in long-term trends include the transition from land-based to marine resources and the decline of small-scale agriculture. Our analysis illuminates the deep connections between local livelihoods and national as well as global political–economic processes, which favour extraction and export of natural resources throughout the period investigated, whereby resource access and market mechanisms create and constrict adaptation options for the villagers. Gradual environmental changes, such as erosion, and episodic events, such as hurricanes, have also influenced livelihood shifts and adaptations in combination with a wide range of political–economic factors. Despite the demonstrated importance of the influence of history and dimensions of political economy on contemporary adaptation options in the communities studied, the literature on climate change adaptation inadequately accounts for these factors. This paper adds new perspectives to current debates in climate change research by emphasising that longer temporal dimensions of livelihood change are important for understanding the current context for adaptation.